Mudanças na base tributária e seus efeitos macroeconômicos em equilíbrio geral: uma aplicação para a economia brasileira - MENEZES, Francisco Marcelo Silva de (1999)
The present dissertation aims to investigate through simulations, the macroeconomic and welfare impacts of the possible paths of the tax reform in Brazil, conjugating the traditional system with the pension system, through a computable general equilibrium model with overlapping generations. Regarding the traditional system, it is taken into consideration the effects of incidence aspects over real economic variables with the adoption of different tax bases. Regarding the pension system, it is considered the gradual substitution of the "pay as you go" system towards a capitalization system. Simulations provide evidence that taxatign - over consumption leads to lower real interest rates, higher investment rates and a higher capital-output ratio, determining higher wage rates, which has positive effects on welíare. These resuIts are optimized when there is the substitution of the "pay as you go" pension system towards a capitalization pension system.